Reading, writing, and repair: the role of ubiquitin and the ubiquitin-like proteins in DNA damage signaling and repair - Pinder, Jordan B.; Attwood, Kathleen M.; Dellaire, Graham (Frontiers in Genetics, 2013)
Genomic instability is both a hallmark of cancer and a major contributing factor to tumour development. Central to the maintenance of genome stability is the repair of DNA damage, and the most toxic form of DNA damage is the DNA double-strand break. As a consequence the eukaryotic cell harbours an impressive array of protein machinery to detect and repair DNA breaks through the initiation of a multi-branched, highly coordinated signaling cascade. This signaling cascade, known as the DNA damage response (DDR), functions to integrate DNA repair with a host of cellular processes including cell cycle checkpoint activation, transcriptional regulation, and programmed cell death. In eukaryotes, DNA is packaged in chromatin, which provides a mechanism to regulate DNA transactions including DNA repair through an equally impressive array of post-translational modifications to proteins within chromatin, and the DDR machinery itself. Histones, as the major protein component of chromatin, are subject to a host of post-translational modifications including phosphorylation, methylation, and acetylation. More recently, modification of both the histones and DDR machinery by ubiquitin and other ubiquitin-like proteins (UBLs), such as the small ubiquitin-like modifiers (SUMOs), has been shown to play a central role in coordinating the DDR. In this review, we explore how ubiquitination and sumoylation contribute to the “writing” of key post-translational modifications within chromatin that are in turn “read” by the DDR machinery and chromatin remodeling factors, which act together to facilitate the efficient detection and repair of DNA damage.